2015
DOI: 10.1111/psyp.12453
|View full text |Cite
|
Sign up to set email alerts
|

Neurological damage disrupts normal sex differences in psychophysiological responsiveness to music

Abstract: Men and women often display different physiological responses to emotional stimuli, and these responses can be affected by brain damage. Here, we investigated how brain damage differentially affects electrodermal responses based on sex. We studied neurologically normal, healthy adults and a sample of neurological patients. Participants listened to music, an emotional stimulus that reliably elicits skin conductance responses (SCRs). Electrodermal activity was recorded while participants listened to musical clip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Although female pupillary reactions were stronger overall, male pupillary reactions differed more as a function of groove, spectral content and metrical structure. Although physiological differences between males and female reactions to music have been documented in a handful of previous studies (McFarland and Kadish, 1991; Altenmüller et al, 2002; Koelsch et al, 2003a,b; Nater et al, 2006; Gingras et al, 2015; Belfi et al, 2016; Laeng et al, 2016), to our knowledge these results constitute the first evidence of sex differences specific to the link between music and movement. Given the culturally limited nature of our sample, the biological implications of such differences are limited.…”
Section: Discussionsupporting
confidence: 48%
“…Although female pupillary reactions were stronger overall, male pupillary reactions differed more as a function of groove, spectral content and metrical structure. Although physiological differences between males and female reactions to music have been documented in a handful of previous studies (McFarland and Kadish, 1991; Altenmüller et al, 2002; Koelsch et al, 2003a,b; Nater et al, 2006; Gingras et al, 2015; Belfi et al, 2016; Laeng et al, 2016), to our knowledge these results constitute the first evidence of sex differences specific to the link between music and movement. Given the culturally limited nature of our sample, the biological implications of such differences are limited.…”
Section: Discussionsupporting
confidence: 48%
“…Researchers reported that both men and women evidenced enhanced P300 amplitudes to negatively valenced pictures, but that this effect was specific to the right hemisphere in males and the left in females (Gasbarri et al, 2007). In addition to normative differences, sex appears to moderate the effects of brain damage on physiological responses to emotional stimuli (Belfi, Chen, Schneider, & Tranel, 2016). Sexually dimorphic associations have also been reported with regard to psychopathology.…”
Section: The Hidden Costs Of Moderationmentioning
confidence: 99%
“…Although damage to different brain structures appeared to have little to no effect on individuals’ skin conductance responses to music, Belfi et al’s (2016) analysis revealed that men with brain damage had reduced SCRs while listening to music, but women with brain damage showed no significant reductions. Yet despite the evidence that similar brain damage can affect men and women in markedly divergent ways, precious little attention is paid to sex effects in neuropsychological research.…”
Section: Discussionmentioning
confidence: 92%
“…Other researchers have noted a distinct lack of behavioral results when ignoring sex differences, yet observed robust effects of brain damage on a psychophysiological measure of emotion when including the variable of sex in their analysis (Belfi et al, 2016). Although damage to different brain structures appeared to have little to no effect on individuals’ skin conductance responses to music, Belfi et al’s (2016) analysis revealed that men with brain damage had reduced SCRs while listening to music, but women with brain damage showed no significant reductions.…”
Section: Discussionmentioning
confidence: 99%